Redução enantiosseletiva de cetonas utilizando fungos endofíticos da Amazônia - Pinheiro, Daniely da Silva (2010)
This study was performed, enantioselective reduction of ketones: p-nitroacetophenone, ethyl acetoacetate, α-chloroacetophenone and zerumbone mediated by endophytic fungi of the Amazon, Saccharomyces cerevisiae (Baker yeast commercial and industrial strains FP, CAT-1 and PE-2 and the resolution of racemic alcohol zerumbol by lipase B from Candida antarctica in organic medium. The ketones were reduced with NaBH4 to racemic alcohols were used as standards for GC analysis. In the enantioselective reduction of p-nitroacetophenone by endophytic fungi the chiral alcohols were obtained with excellent results in 72 hours, the alcohols had good conversion percentage (87% to CF02_03, 61% to CF03_05) and high enantiomeric excess (ee) (97% and 91%). Fungi that showed higher enantioselectivities were strains CF02_03 and CF03_05. These microorganisms were able to selectively form enantiomerically pure alcohols, and the strain CF02_03 quite selective for the formation of one isomer and the strain CF03_05 was selective for the other enantiomer. In the reactions of reduction of ethyl acetoacetate, the endophytics have produced an unwanted product in 24 hours of reaction. The fungus CF03_05 obtained the highest conversion (78%) of the product in 72 hours. The reduction reactions of α-chloroacetophenone were performed with the strains CG05_04 and CF03_04. Chirals alcohols produced in 72 hours with conversions showed of 19% and 26% respectively, and good enantiomeric excesses (23% and 47%). In the reactions of reduction of ethyl acetoacetate mediated FP was obtained in 36h and a conversion of 0.85% and 26% ee. In the reactions of reduction of ethyl acetoacetate using industrial strains of Saccharomyces cerevisiae, CAT-1 and PE-2, has been a higher conversion and ee, highlighting the reaction with strain PE-2, 36h, we obtained 45 % conversion and ee of >99%, although another strain with the CAT-1 was obtained from a low conversion of 24% and ee> 99%. In the reduction reaction of p-nitroacetophenone using the peel and pulp of tucumã found that the formation of alcohols in 48 hours, and the highest conversion (86%) was obtained from the bark and the highest ee (46%) was obtained from the pulp. According to data in the literature, the formation of alcohols is probably due to the presence of endophytic fungi or enzymes of the fruit. The enantioselective reduction of zerumbone not occurred when it was used endophytic fungi, baker yeast and tucumã. However, there was the resolution of racemic zerumbol with enzyme Novozyme 435 resulting in good conversion (50%), high enantiomeric excess (>99 and >99%) and enantiomeric ratio >200. In general, we obtained very promising results with alternative biocatalysts for enantioselective reduction of ketones with high enantiomeric excess and conversion. One result that stood out was the selectivity of two fungal strains where the enantiomers were formed distinctly with each of the strains. With this result we can visualize the exploration of different biocatalysts with different enantioselectivities for the same reaction. Keywords: Amazon; endophytic fungi; chirals alcohols; bioreduction